Prognostic value of the donor‐derived cell‐free DNA assay in acute renal rejection therapy: A prospective cohort study. Issue 10 (4th September 2020) - Shen, Jia; Guo, Luying; Yan, Pengpeng; Zhou, Jingyi; Zhou, Qin; Lei, Wenhua; Liu, Haitao; Liu, Guangjun; Lv, Junhao; Liu, Feng; Huang, Hongfeng; Dong, Wenzhao; et al.
Abstract: Donor‐derived cell‐free DNA (dd‐cfDNA) is a promising biomarker for monitoring allograft status. However, whether dd‐cfDNA can reflect real‐time anti‐rejection treatment effects remains unclear. We prospectively recruited 28 patients with acute renal rejection, including 5 with ABMR, 12 with type IA or type IB rejection, and 11 with type IIA or IIB rejection. dd‐cfDNA levels in peripheral blood were measured using human single nucleotide polymorphism (SNP) locus capture hybridization. The percentage of dd‐cfDNA (dd‐cfDNA%) declined significantly from 2.566 ± 0.549% to 0.773 ± 0.116% ( P < .001) after anti‐rejection therapy. The dd‐cfDNA% decreased steadily over the course of 3 days with daily methylprednisolone injections, but no significant difference in the dd‐cfDNA% was observed between the end of anti‐rejection therapy and 2 weeks later. Changes in the dd‐cfDNA% (∆dd‐cfDNA%) demonstrated a positive correlation with estimated glomerular filtration rates at 1 month ( ρ = 2.570, P = .022), 3 months ( ρ = 3.210, P = .027), and 6 months ( ρ = 2.860, P = .019) after therapy. Thus, the dd‐cfDNA assay shows prognostic capabilities in therapy outcome and allograft recovery; however, its ability is inhibited by methylprednisolone regardless of the types of rejection. Additionally, a reassessment of frequency intervals for testing is required.